Elevated levels of exogenous prolactin promote inflammation at the maternal-fetal interface via the JAK2/STAT5B signaling axis - Alycia Williams; Daniel J. Hossack; Nia Thompson; Yul Eum Sim; Cristina Wilson; Viviane Schuch; Tiffany Hailstorks; Rana Chakraborty; Erica L. Johnson; Erica L. Johnson; Erica L. Johnson (Frontiers in Immunology)
The placenta is a unique organ with various immunological and endocrinological roles that modulate maternal and fetal physiology to promote maternal-fetal tolerance, pregnancy maintenance, and parturition at term. During pregnancy, the hormone prolactin (PRL) is constitutively secreted by the placenta and is necessary for implantation, progesterone support, fetal development, and overall immune modulation. While PRL is essential for pregnancy, studies suggest that elevated levels of serum PRL (hyperprolactinemia) are associated with adverse pregnancy outcomes, including miscarriage, preterm birth, and preeclampsia. However, there is a lack of mechanistic studies to support these observations. Here we investigated the impact of elevated levels of PRL on placental cells and evaluated PRL effects on the JAK2/STAT5 inflammatory signaling cascade. Elevated levels of exogenous PRL enhances PRL and PRL-receptor expression, along with JAK2/STAT5 signaling in primary decidual mononuclear cells and the placental trophoblast cell line, JEG-3. Following PRL exposure, the STAT5 isoform, STAT5B, is preferentially activated and there is a significant upregulation in the secretion of pro-inflammatory cytokines, IL-6 and IL-1β. This inflammatory cascade is supported via PRL-induced reduction of SOCS1 and SOCS2. Furthermore, LPS exacerbates PRL expression and JAK2/STAT5 signaling, leading to increased secretion of IL-6 and TNF-α. These results highlight the inflammatory roles of elevated PRL at the maternal-fetal interface, underscoring the need for further mechanistic studies to elucidate its functions in pregnancy.